Dosimetric verification of enhanced dynamic wedges by a 2D ion chamber array - Oh, Se An; Kim, Sung Kyu; Kang, Min Kyu; Yea, Ji Woon; Kim, Eng Chan (Journal of the Korean Physical Society, 2013)
Wedge filters are commonly used to achieve dose uniformity in the target volume in radiotherapy and can be categorized as physical wedges (PWs) and enhanced dynamic wedges (EDWs). The EDW generates PW-like dose profiles while moving the upper jaw in the Y directions with a varying dose rate in the treatment beams. Task Group 53 of the AAPM (American Association of Physicists in Medicine) recommended that the dynamic wedge be verified before implementation in the radiation treatment planning (RTP) system. The aim of this study was to use the I’mRT MatriXX to verify the dose profiles of the EDWs manufactured by Varian. We used Pencil Beam Convolution algorithms (eclipse 8.6) for the calculation and I’mRT MatriXX with Plastic Water® phantom MULTICube for dose measurements. The gamma indices of the calculations and the measurements for the EDWs were 84.84% and 86.54% in 2%/2 mm tolerance, and 99.47% and 99.64% in 3%/3 mm tolerance for wedge angles of 15°, 30°, 45° and 60°, respectively. The dose distributions differed between the calculations using the system and the measurements in the penumbra and the outer beam regions of the wedge fields. We confirmed that the dosimetric verifications of the EDW were acceptable when using the criterion for external beam dose calculations of Task Group 53.